PEMANFAATAN TEKNOLOGI LIDAR DALAM ANALISIS GENANGAN BANJIR AKIBAT LUAPAN SUNGAI BERDASARKAN SIMULASI MODEL HIDRODINAMIK - M. Baitullah Al Amin (Universitas Lambung Mangkurat, 2015)
Flood analysis requires accurate topographic data to obtain a good overview of flood inundation. At this time, LIDAR (Light Detection and Ranging) is the best technology of remote sensing for collecting elevation data from earth surface. This elevation data can be used to create relief of the earth’s surface in three-dimensional format which is often referred to as a digital elevation model (DEM).This paper dealt with the utilization of LIDAR technology in analysis of flood inundation due to overflowing river based on simulation of hydrodynamic model. The creation of DEM from elevation data was done by geographic information system technique using Global Mapper software. The river geometry model was established by using HEC-GeoRAS installed in ArcGIS which then water surface profiles of flood were simulated using HEC-RAS.The result of flood profiles simulation were imported into HEC-GeoRAS in order to obtain flood inundation map. The utilization of LIDAR technology is very helpful within analysis of flood inundation, so that the availability and its access need to be improved. Key words: LIDAR, DEM, HEC-GeoRAS, HEC-RAS, Flood Simulation